Conceptual and Methodological Pitfalls in Experimental Studies: An Overview, and the Case of Alzheimer’s Disease - Puzzo, Daniela; Conti, Fiorenzo (Frontiers in Molecular Neuroscience, 2021)
The main goal of scientific research is to uncover new knowledge to understand reality. In the field of life sciences, the aim of translational research – to transfer results “from bench to bedside” – has to contend with the problem that the knowledge acquired at the “bench” is often not reproducible at the “bedside”, raising the question whether scientific discoveries truly mirror the real world. As a result, researchers constantly struggle to overcome the dichotomy between methodological problems and expectations, as funding agencies and industries demand expandable and quick results whereas patients, who are uninterested in the epistemological dispute, only ask for an effective cure. Despite the numerous attempts made to address reproducibility and reliability issues, some essential pitfalls of scientific investigations are often overlooked. Here, we discuss some limitations of the conventional scientific method and how researcher cognitive bias and conceptual errors have the potential to steer an experimental study away from the search for the vera causa of a phenomenon. As an example, we focus on Alzheimer's disease research and on some problems that may have undermined most of the clinical trials conducted to investigate it.